Towards Large-area Photovoltaic Nanocells: Experiences Learned from Smart Window Technology - Carl M Lampert (Solar Energy Materials and Solar Cells, 1994)
This investigation covers two technologies which have different applications but have many similar characteristics. One is the nanocell photoelectrochemical solar cell, the other is the electrochromic window. At first it is hard to see what they have in common other then that they both interact with light.